Characterization of the biologic therapy used by patients with Psoriasis and Psoriatic Arthritis treated in HDS. - Espírito Santo, Margarida (2011)
Psoriasis is chronic, immune-mediated, infflamatory, multi-system disease, which manifests predominantly in the skin and at the joint.